SISTEM INFORMASI PEMESANAN DENGAN PENERAPAN KONSEP ELECTRONIC CUSTOMER RELATION MANAGEMENT BERBASIS WEB - I Dewa Ayu Eka Yuliani; Susanti Margaretha Kuway (Universitas Raharja, 2017)
Building customer loyalty at Multi Sport Pontianak requires corporations to create new, innovative, and differentiated products. Quality assurance is one of the most important aspect beside employing technology to provide better information to customers and also better before and after sales services. This research employs research and development method to design E-CRM with sequential Linear and Unified Modelling Language as tools for system modelling. Ordering information system design with E-CRM helps store users to build better customer loyalty with uptodate information and promotion to targeted customer. By listening to customer, better customer loyalty will be achieved. E-crm provides better understanding of customers with its real time interaction during sales process. This feature enables corporations to build better products and services and in the end creates better customer loyalty.